Review on maintenance issues toward building maintenance management best practices - Nur'afini, Dzulkifli; Noor Nabilah, Sarbini; Izni Syahrizal, Ibrahim; Nur Izieadiana, Abidin; Fadzil, Mat Yahaya; Nik Zainab, Nik Azizan (Elsevier Ltd, 2021)
Buildings deteriorate gradually over time due to several reasons, including unattended defects, neglected damage, and natural causes. Hence, maintenance activities are required to impede the deterioration process to ensure the continuous function of the buildings. Maintenance is a systematic process to safeguard features and resources operated at optimum levels to achieve building standards and performance. Nevertheless, previous studies have shown that maintenance practices in Malaysia were not implemented efficiently and performed far below maintenance best practices. Hence, this study aimed to explore the building maintenance practice issues in Malaysia. A systematic literature review (SLR) was conducted to examine the issues or factors that affect building maintenance practice. The review included articles on issues affecting building maintenance practice and recommendations to minimize the issues. The maintenance practice issues were categorized into planning, management, staff, competency, technology, and technical capabilities. Besides, the study proposed recommendations from the literature for future studies aligning with the ISO 41001 guidelines. Finally, a conceptual framework was proposed toward building maintenance management best practices at the end of the study.